The Meaning of Concepts of Human Nature in Organizational Life in Business Ethics Context - Horodecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2014)
The main goal of this paper is to exhibit the role of the concept of human nature for the ethical orientation of organizational life. Therefore, after presenting some definitions of the concepts of human nature, which depict the complexity of these phenomena, some models of the concepts of human nature are described. Furthermore, the setting of the concepts of human nature in the organizational life is discussed. Those concepts can be perceived as a deep-structure of the organizational life, having an impact not only on the individual behaviour of employees and managers (like sensibility for human emotions, pro-social engagement, communication style), but also affecting their moral competence and influencing whole organizational culture – image of the organization, preferred management strategies and the way of perceiving justice. Those elements play crucial role in ethical attitude of the organization because all those variables support the efficacy of ethical rules and most of them are part of ethical code and corporate ethical code. Therefore, it is necessary for an organization to consider implicit and explicit concepts of human nature on which the organizational culture is based and support those concepts, which enables the ethical conduct of the organization and being alert especially to the consequences of materialistic/egoistic and competitive concepts of human nature. The theses discussed in the paper are supported by some empirical research studies conducted in this field.